Discovering support needed for startups in their early stages using on Penta Helix framework - Kiki Sudiana; Ernie Tisnawati Sule; Imas Soemaryani; Yunizar Yunizar (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
Startup companies are expected to become the new engines of economic growth through the rise of new innovation- based entrepreneurs. The Penta Helix framework is widely used as a framework to analyse factors related to the development of innovation-based companies. The use of the Penta Helix framework as the unit of analysis is considered to be relevant because this framework offers a comprehensive perspective and is in line with the economic development innovation and knowledge-based startups. However, there is a lack of research that has been conducted that analyse the nature of support that can be given to startups at their early-stage of creation using the Penta Helix framework that consists of five stakeholders namely Academicians, Businessmen, Government, Communities. This study aims to propose a conceptual model about the nature of support needed by startups in order to survive in their initial stages by using the Penta Helix Framework. This study is a qualitative one using the Focus Group Discussion method, in which participants are made of six early stages technology-based startup founders and CEOs, who were gathered to conduct several discussions regarding the topics. Our results show that obstacles faced by startups include among other: difficulties in obtaining qualified yet affordable workforce in facing existing competitors, difficulties in increasing sales, difficulties in managing product development costs, no adequate support from the government, and ineffective incubation programs. A model that consists of lists of support that startups need, was depict as main contribution from the discussion, named Penta Helix support for startups. This model offers comprehensive practical guide for policy makers to support startups from five perspectives.
Keywords: M10; M13; O10; O11; E60; 650; startups challenges; support for startups; Penta Helix; focus group discussion